1016 The Impact Of COVID-19 On Prostate Cancer: Is This the Calm Before the Storm?. (12th October 2021) - McCauley, N; Rashid, M; Wilson, J; Carter, A; Cox, A
Abstract: Aim: Cancer treatment targets were halted in the COVID-era due to a major re-organisation of services and coincided with a drop in prostate cancer (PCa) referrals, investigations, and diagnoses. This study measures the impact of the pandemic on a PCa diagnostic pathway in a major cancer centre. Method: Data was collected during the onset of COVID-19 (March to June 2020) and the same months in 2019 for urgent suspected prostate cancer (USPC) referrals. All referrals, PSA tests, multiparametric MRI's of prostate (mpMRI-P), and TRUS-guided biopsy of the prostate (TBP) were recorded. Results: USPC referrals reduced by 65% from a mean 315 referrals per month to 110 during the pandemic. During March-June 2019 a total of 10, 404 PSA tests were conducted in the healthcare trust, which reduced by 39% during COVID-19. Multiparametric MRI of prostate was reduced by 45%. TRUS biopsies were down by 65%, from a mean of 31 to 11 biopsies per month, with only 3 biopsies being conducted in April 2020. Conclusions: The reduction in PCa referrals and workload in our centre in the COVID-era has been significant. The uncertainty associated with such a drop in demand poses concerns for meeting future cancer targets when prostate cancer referrals return to baseline.